Diagnostic value of effluent endotoxin level in gram-negative peritonitis in CAPD patients - (:unkn) unknown (Multimed Inc., 2001)
◆ Objective: To evaluate the diagnostic usefulness of effluent endotoxin by Limulus amoebocyte lysate (LAL) assay in gram-negative peritonitis patients on continuous ambulatory peritoneal dialysis (CAPD) therapy. ◆ Design: Prospective study with patients serving as their own controls. Standard microbiologic work up and endotoxin analysis of effluents (night dwell) were done during the pre- and posttreatment phases. ◆ Setting: Specimens from three teaching hospitals were processed and tested at a common center. Patients were left for treatment at their respective centers without intervention. ◆ Patients: 32 clinical peritonitis and 40 infection-free CAPD patients were studied. ◆ Results: 75% (n = 24) of cultures were positive: 41.6% (n = 10) gram-negative and 58.4% (n = 14) gram-positive bacteria. Effluents of pre- and post treated gram-negative cultures had endotoxin levels of 1.53 ± 0.169 and 0.214 ± 0.085 endotoxin units (EU)/mL, respectively (p < 0.0001); pre- and posttreated gram-positive levels of 0.102 ± 0.06 and 0.122 ± 0.052 EU/mL, respectively (p > 0.05); pre- and posttreated culture-negative peritonitis levels of 0.110 ± 0.025 and 0.087 ± 0.031 EU/mL, respectively (p > 0.05); peritonitis-free effluents contained 0.117 ± 0.079 EU/mL. The diagnostic specificity and the sensitivity of LAL assay were 100% and 98.2% respectively. ◆ Conclusion: Where initial microbiological work-up cannot demonstrate a pathogen, effluent endotoxin determined by quantitative LAL assay is a useful marker for diagnosis and management, within safe time limits, of gram-negative peritonitis in CAPD patients.
Keywords: Endotoxin; Gram-negative bacteria; LAL; Limulus amoebocyte lysate; Peritonitis